High‐Frequency Submesoscale Motions Enhance the Upward Vertical Heat Transport in the Global Ocean. Issue 9 (4th September 2020) - Su, Zhan; Torres, Hector; Klein, Patrice; Thompson, Andrew F.; Siegelman, Lia; Wang, Jinbo; Menemenlis, Dimitris; Hill, Christopher
Abstract: The rate of ocean heat uptake depends on the mechanisms that transport heat between the surface and the ocean interior. A recent study found that the vertical heat transport driven by motions with scales smaller than 0.5° (submesoscales) and frequencies smaller than 1 day −1 is upward. This transport competes with the other major components of the global heat transport, namely, the downward heat transport explained by the large‐scale wind‐driven vertical circulation and vertical diffusion at small scales and the upward heat transport associated with mesoscale eddies (50‐ to 300‐km size). The contribution from motions with small spatial scales (<0.5°) and frequencies larger than 1 day −1, including internal gravity waves, has never been explicitly estimated. This study investigates this high‐frequency (subdaily) submesoscale contribution to the global heat transport. The major result of this study, based on the analysis of a high‐resolution ocean model, is that including this high‐frequency contribution surprisingly doubles the upward heat transport due to submesoscales in winter in the global ocean. This contribution typically concerns depths down to 200–500 m and can have a magnitude of up to 500 W m −2 in terms of wintertime heat fluxes at 40‐m depth, which causes a significant upward heat transport of ~7 PW when integrated over the global ocean. Thus, such submesoscale heat transport, which is not resolved by climate models, impacts the heat uptake in the global ocean. The mechanisms involved in these results still need to be understood, which should be the scope of future work. Key Points: Ocean heat flux is large at high frequency Such high‐frequency flux is generated at submesoscale Such heat flux is a key component of global heat budget